1990
DOI: 10.1113/jphysiol.1990.sp018203
|View full text |Cite
|
Sign up to set email alerts
|

Control of intracellular calcium by ATP in isolated outer hair cells of the guinea‐pig cochlea.

Abstract: SUMMARY1. Intracellular calcium levels were monitored in isolated outer hair cells of the guinea-pig cochlea using the calcium-sensitive dye Fura-2.2. The calcium in the cells was studied during application of ATP externally applied from a pipette. ATP induced a rise of intracellular calcium which could be separated into two components: a rapid rise, peaking in 20 s, localized around the apical end of the cell, and a slower rise, peaking in 50-150 s but spread throughout the cell. The effects were observed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 40 publications
3
93
1
Order By: Relevance
“…It has been demonstrated previously that the application of ATP to isolated cochlear hair cells elicits an inwardly rectifying current by gating a nonselective cation channel (Ashmore and Ohmori, 1990;Nakagawa et al, 1990;, 1993bLin et al, 1993. This study has shown that TNP-ATP blocks this current, thus establishing, at least in cochlear hair cells, that this analog is a more effective antagonist of ATP binding to purinergic receptor sites than the competitive P, purinoceptor antagonist suramin (Dunn and Blakeley, 1988;Nakazawa et al, 1990, 199 1;Henning et al, 1992;Silinsky et al, 1992).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It has been demonstrated previously that the application of ATP to isolated cochlear hair cells elicits an inwardly rectifying current by gating a nonselective cation channel (Ashmore and Ohmori, 1990;Nakagawa et al, 1990;, 1993bLin et al, 1993. This study has shown that TNP-ATP blocks this current, thus establishing, at least in cochlear hair cells, that this analog is a more effective antagonist of ATP binding to purinergic receptor sites than the competitive P, purinoceptor antagonist suramin (Dunn and Blakeley, 1988;Nakazawa et al, 1990, 199 1;Henning et al, 1992;Silinsky et al, 1992).…”
Section: Discussionmentioning
confidence: 67%
“…Studies have shown that extracellularly applied ATP can elicit changes in intracellular Ca2+ concentrations and transmembrane ion conductance in isolated hair cells (Ashmore and Ohmori, 1990;Nakagawa et al, 1990;Shigemoto and Ohmori, 1990;Dulon et al, 1991;Housley et al, , 1993aAshmore et al, 1993). These effects are consistent with a P, purinoceptor classification.…”
mentioning
confidence: 99%
“…In the cochlea, it has been reported that ATP can evoke inward currents and raise the intracellular Ca ++ concentration in the outer and inner hair cells, thereby modifying sound transduction and neurotransmission [10][11][12][13]. ATP can activate purinergic (P2) receptors to produce inward cationic currents [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…ATP has been described as a neurotransmitter or a neuromodulator in auditory neurotransmission. ATP has been reported to induce an increase of intracellular Ca 2+ concentration ([Ca 2+ ] i ) in outer hair cells (OHCs) [4,5], inner hair cells (IHCs) [6][7][8], spiral ganglion neurons (SGNs) [9,10], and supporting cells [11][12][13]. These previous studies suggested that ATP may affect auditory neurotransmission by modulating [Ca 2+ ] i in the cochlear cells.…”
Section: Introductionmentioning
confidence: 99%